2014
DOI: 10.1016/j.pediatrneurol.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurodevelopmental Screening in Tuberous Sclerosis Complex: A Potential Window of Opportunity

Abstract: BACKGROUND Infants born with tuberous sclerosis complex (TSC), a genetic condition resulting from a mutation in TSC1 or TSC2, are at increased risk for intellectual disability and/or autism. Features of epilepsy, neuropathology, genetics as well as timing and type of mechanism-based medications have been proposed as risk factors. Neurodevelopmental outcomes have been reported among these studies; however, few include data about the individuals’ early neurodevelopmental profile, a factor that may contribute sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Besides of these neurological disorders, brain tumors (gliomas, ependymomas and medulloblastomas) also have a close relationship with the abnormalities of brain regional NSC/progenitor cell populations during development in children [ 13 39 40 ]. In general, both developmental disorders and pediatric brain tumors are diagnosed in early developmental stages and childhood [ 41 42 43 44 ] raising a possibility that the NSC/progenitor cell populations rather than differentiated brain cells could have an implication in disease phenotypes. Although the causing factors of the diseases are not fully uncovered, there are several known genetic factors which are commonly found in the patients with learning disability, autism, epilepsy and pediatric brain tumors.…”
Section: The Implication Of Mtor Activity In Brain Developmental Disomentioning
confidence: 99%
“…Besides of these neurological disorders, brain tumors (gliomas, ependymomas and medulloblastomas) also have a close relationship with the abnormalities of brain regional NSC/progenitor cell populations during development in children [ 13 39 40 ]. In general, both developmental disorders and pediatric brain tumors are diagnosed in early developmental stages and childhood [ 41 42 43 44 ] raising a possibility that the NSC/progenitor cell populations rather than differentiated brain cells could have an implication in disease phenotypes. Although the causing factors of the diseases are not fully uncovered, there are several known genetic factors which are commonly found in the patients with learning disability, autism, epilepsy and pediatric brain tumors.…”
Section: The Implication Of Mtor Activity In Brain Developmental Disomentioning
confidence: 99%
“…The current study describes a case of multiple cardiac rhabdomyomas confirmed by routine echocardiogram screening in week 31 of pregnancy. The infant experienced seizures in the neonatal period (2 weeks of age), which is earlier than previously reported cases in which the onset was 1 month of age ( 14 ). Genetic mutation analysis revealed a novel mutation in TSC2.…”
Section: Introductionmentioning
confidence: 50%
“…Ressalta-se a importância de investigar pacientes com sinais potenciais de CET com o objetivo de realizar diagnóstico precoce. Tem-se, inclusive, discutido a importância da intervenção precoce como forma de melhorar o prognóstico 29,30 .…”
Section: Discussionunclassified